Conceptual Directions of the Process of Preparing Future Teachers Based on the Analysis of Foreign Experience (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is dedicated to the topical issue of preparing future teachers. The article offers a series of conclusions and recommendations for optimizing the process of educating future teachers, focusing on the need to harmonize educational standards, strengthen the practical orientation of training, and ensure continuous professional development of educators. The research results can be useful for developers of educational programs, educators, methodologists, and all those interested in improving the system of teacher training.